EFEKTIVITAS PELAKSANAAN SIDANG KELILING DALAM ALTERNATIF PENYELESAIAN SENGKETA BERDASARKAN PRINSIP HUKUM ACARA PERDATA CEPAT, SEDERHANA DAN BIAYA RINGAN - Ayuna Putri, Sherly; Kusmayanti, Hazar; Rachmainy, Linda (Institut Hindu Dharma Negeri Denpasar, 2018)
In recent years, religious court tries to break the gap by means of roving or mobile court. Mobile court is applied to fill up sense of justice and right among citizen who do not have adequate knowledge about procedural law and live away from city center where court usually runs. This research is attempted to dig into the practices of mobile court and compare it with other principles of procedural laws in Indonesia civil code.This research is used juridical-normative method that emphasizes investigation into law provision that is valid in Indonesia jurisdiction. The investigation will be addressed to Het Herziene Indonesisch Reglement (HIR), Legislation no 48 of 2009 on judiciary dominion, Legislation no 3 of 2015, Legislation no 50 of 2009 on religious court, and Supreme Court Legislation no 1 of 2015 on integrated service of mobile court in district court and religious court or Islamic court in order to publication of marriage certificate. This research is specifically analytical-descriptive in character and in order to obtain holistic description about practice of dispute settlement in Islamic court by means of mobile court in accordance to principles and codes of civil code procedural law. The result of this description then to be analyzed by means of qualitative-normative method on the ground of document research in which materials of legislation and jurisprudence are analyzed furthermore. This research also use observation and interview as complementary method, especially on how Tasimalaya District Court and Cimahi Religious Court practicing mobile court.